EMERGENCY MANAGEMENT OF CHOKING IN CHILDREN: LITERATURE REVIEW - Khayudin, Bayu Akbar; Kusyani, Asri (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2025)
Background: Choking is an emergency that often occurs in society, especially in children. This is because children's characteristics and behavior vary at that age and need to be understood and supervised by parents, especially mothers. Knowledge about handling choking will influence community behavior in handling choking and avoiding the threat of death in children. Choking can block the human airway, especially in children. One effort to increase community knowledge is through training. Objective: The aim is to evaluate existing research on the effectiveness of training interventions in improving parental and caregiver knowledge and skills in managing choking emergencies in children. Design: This study employs a literature review approach to evaluate the effectiveness of training interventions in improving parents' and caregivers' knowledge and skills in managing choking emergencies in children. Data Sources: The data sources for this study consist of national and international journals relevant to the emergency management of choking in children. The articles were obtained from electronic databases such as Google Scholar, PubMed, ScienceDirect, and Scopus, covering publications from 2019 to 2024. Review Methods: The literature search was conducted using the keywords